2015
DOI: 10.5194/gmd-8-2447-2015
|View full text |Cite
|
Sign up to set email alerts
|

PLUME-MoM 1.0: A new integral model of volcanic plumes based on the method of moments

Abstract: Abstract. In this paper a new integral mathematical model for volcanic plumes, named PLUME-MoM, is presented. The model describes the steady-state dynamics of a plume in a 3-D coordinate system, accounting for continuous variability in particle size distribution of the pyroclastic mixture ejected at the vent. Volcanic plumes are composed of pyroclastic particles of many different sizes ranging from a few microns up to several centimeters and more. A proper description of such a multi-particle nature is crucial… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 39 publications
3
38
0
Order By: Relevance
“…6, the effect of particle size is visible only for windless conditions and particles in the millimetric range. This result is consistent with the works of Woods and Bursik (1991) de' Michieli Vitturi et al (2015) Pouget et al (2016), who found negligible variations of the column height with mean grain size in the range (-6 ≤ Φ ≤ 0). In contrast, because of a different assumption on the grain size distribution Fig.…”
Section: Effect Of Particle Size Variations On Heightsupporting
confidence: 95%
“…6, the effect of particle size is visible only for windless conditions and particles in the millimetric range. This result is consistent with the works of Woods and Bursik (1991) de' Michieli Vitturi et al (2015) Pouget et al (2016), who found negligible variations of the column height with mean grain size in the range (-6 ≤ Φ ≤ 0). In contrast, because of a different assumption on the grain size distribution Fig.…”
Section: Effect Of Particle Size Variations On Heightsupporting
confidence: 95%
“…Another possible approach is the method of moments, in which the evolution of the moments of the grain size distribution is described. This has recently been applied in volcanology to integral plume models by de' Michieli Vitturi et al (2015). In the present work we opted for the classical discretization of the grain size distribution (see Neri et al, 2003).…”
Section: The Eulerian Model In "Mixture" Formulationmentioning
confidence: 99%
“…Two types of model exist, one-dimensional integral models, which evaluate plume rise along a centre line, solving equations for conservation of mass, momentum and thermal energy along that line (e.g. Plumeria: Mastin [6]; PlumeRise: Woodhouse et al [49]; PlumeMom: de' Michieli Vitturi [53]), and 3D models, which account for more complex interactions between the rising plume and the atmosphere (e.g. ATHAM: Herzog et al [54]; ASHEE: Cerminara et al [55]).…”
Section: Insights From Modelling: Case Study 3-results From Sensitivimentioning
confidence: 99%